Stock market volatility, speculation and unemployment: A Granger-causality analysis - Algieri, Bernardina; Brancaccio, Emiliano; Buonaguidi, Damiano (PSL Quarterly Review, 2020)
This study investigates the possible Granger-causal relations between stock price volatility and dividend dynamics on the one hand, and speculation and unemployment on the other. The analysis is carried out for the US over the period 1982-2018. Stock price volatility is calculated in terms of “conditional” volatility and in terms of the so-called “Shiller ratio”, while speculative trading is expressed as “scalping” activities. We find that there is a causal positive relation from speculation to stock price volatility. Furthermore, we show that there is an inverse causal relationship ranging from stock prices to unemployment, while there is no causal relationship between dividends and unemployment. These results corroborate the empirical analyses by Shiller and other authors which deny the traditional Present Value Model (PVM), provide new elements on the possible determinants of stock price volatility, and offer new interpretations of the potential links between the stock market and macroeconomic dynamics. JEL codes: C10; E39; G15